Common Infections in Intensive Care Units, Gram-negative Microorganisms, Antibiotic Resistance - Şenol, Arzu; Balın, Şafak Özer (Kahramanmaras Sutcu Imam University, 2021)
Objective: The aim of the study was to determine the distribution of E.coli, K pneumoniae, P.aeruginosa, and A.baumannii strains isolated from various clinical samples of patients hospitalized in intensive care units (ICUs) as well as the drug resistance rates and the change of these rates over the years, thus contributing to rational antibiotic use and prevention of resistance. Material and Methods: The resistance rates of the isolated strains against colistin, tigecycline, meropenem, imipenem, and trimethoprim-sulfamethoxazole were retrospectively analyzed. Identification and antibiotic susceptibility tests of the microorganisms were done using the VITEK 2 Compact and MicroScan WalkAway 96 automated system (microtube dilution for colistin) and evaluated according to the Clinical and Laboratory Standards Institute recommendations. Results: The most common microorganism in ICUs was A. baumannii (52.2%). As hospital infections, 94.1% ventilator-associated pneumonia, 45.2% central venous catheter-related bloodstream infection, and 44% catheter-related urinary system infection were observed. Meropenem, imipenem, and trimethoprim-sulfamethoxazole resistance rates were found to be high in A. baumannii, P. aeruginosa, and K. pneumoniae. The antibiotic with the lowest resistance rate against all microorganisms was colistin. Conclusion: Since the most susceptible antimicrobial agent is colistin, it can be used alone or in combination with other antibiotics, especially against highly drug-resistant strains. For E. coli infections, carbapenems and trimethoprim-sulfamethoxazole can be used in susceptible strains. Starting treatment and following regular surveillance according to the antibiotic susceptibility test results will contribute to the selection of appropriate antibiotic combinations in ICUs and the reduction of resistant microorganisms.

Amaç: Yoğun bakım ünitelerinde yatan hastaların çeşitli klinik örneklerinden izole edilen Escherichia coli, Klebsiella pneumoniae, Pseudomonas aeruginosa ve Acinetobacter baumannii’nin dağılımlarının, ilaç direnç oranlarının ve bu oranların yııllara göre değişiminin saptanması, böylece akılcı antibiyotik uygulaması ve direncin önlenmesine katkı sağlanması amaçlanmıştır. Gereç ve Yöntemler: İzole edilen suşların kolistin, tigesiklin, meropenem, imipenem ve trimetoprim-sülfametoksazol direnç oranları retrospektif olarak incelenmiştir. Üreyen bakterilerin identifikasyonu ve antibiyotik duyarlılık testleri VITEK 2 Compact ve MicroScan WalkAway 96 otomatize sistemi (kolistin için mikrotüp dilüsyon ) kullanılarak belirlenmiş ve Clinical and Laboratory Standards Institute (CLSI) önerilerine göre değerlendirilmiştir. Bulgular: Yoğun bakım ünitelerinde en sık gözlenen mikroorganizma A. baumannii (%57.2) olarak saptanmıştır. Hastane enfeksiyonu olarak ventilatörle ilişkili pnömoni (%94.1), santral venöz kateterle ilişkili kan dolaşım enfeksiyonu (%45.2) ve kateter ilişkili üriner sistem enfeksiyonu (%44) görülmüştür. A.baumannii, P.aeruginosa ve K.pneumoniae’da meropenem, imipenem ve trimetoprim-sülfametoksazol direnç oranları yüksek bulunmuştur. Tüm mikroorganizmalara karşı en düşük direnç oranına sahip antibiyotiğin kolistin olduğu saptanmıştır. Sonuç: En yüksek duyarlılığa sahip antimikrobiyalin kolistin olması nedeniyle özellikle çok ilaca dirençli suşlara karşı kolistin tek başına veya diğer antibiyotiklerle kombine olarak kullanılabilir. E.coli’de karbapenemler ve trimetoprim-sülfametoksazol duyarlı suşlarda kullanılabilir. Antibiyotik duyarlılık test sonuçlarına göre tedavi başlanması ve düzenli sürveyans takibinin yapılması, yoğun bakım ünitelerinde uygun antibiyotik kombinasyonları seçilmesine ve dirençli mikroorganizmaların azaltılmasına katkı sağlayacaktır.
Yoğun Bakım Ünitelerinde Sık Görülen Enfeksiyonlar, Gram-negatif Mikroorganizmalar, Antibiyotik Direnci
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi